Unravelling the Molecular Mechanisms Underlying the Protective Effect of Lactate on the High-Pressure Resistance of Listeria monocytogenes - Serra-Castelló, Cristina (Biomolecules, 2021)
Formulations with lactate as an antimicrobial and high-pressure processing (HPP) as a lethal treatment are combined strategies used to control L. monocytogenes in cooked meat products. Previous studies have shown that when HPP is applied in products with lactate, the inactivation of L. monocytogenes is lower than that without lactate. The purpose of the present work was to identify the molecular mechanisms underlying the piezo-protection effect of lactate. Two L. monocytogenes strains (CTC1034 and EGDe) were independently inoculated in a cooked ham model medium without and with 2.8% potassium lactate. Samples were pressurized at 400 MPa for 10 min at 10 °C. Samples were subjected to RNA extraction, and a shotgun transcriptome sequencing was performed. The short exposure of L. monocytogenes cells to lactate through its inoculation in a cooked ham model with lactate 1h before HPP promoted a shift in the pathogen’s central metabolism, favoring the metabolism of propanediol and ethanolamine together with the synthesis of the B12 cofactor. Moreover, the results suggest an activated methyl cycle that would promote modifications in membrane properties resulting in an enhanced resistance of the pathogen to HPP. This study provides insights on the mechanisms developed by L. monocytogenes in response to lactate and/or HPP and sheds light on the understanding of the piezo-protective effect of lactate.